Core–shell structure of carbon nanohorns and pH-sensitive liposome for doxorubicin and tumor-associated macrophage polarization factor interleukin-21 codelivery - Zhang, Xiao Xue; Tong, Ge; Shen, Dan; Li, Xue Cheng; Lan, Li Jing; Liu, Xin; Cui, Jing Hao; Huang, Renyu; Lee, Beom Jin; Gao, Hong; Cao, Qing Ri (Journal of Drug Delivery Science and Technology, 2023)
The combination of immunotherapy and chemotherapy is becoming a very promising cancer treatment method. However, the effective delivery of chemical drug or immune molecule to targeting tissues is a scientific issue to be solved urgently. A novel core–shell structure of single-walled carbon nanohorns (SWCNHs) and pH-sensitive liposome (PSL) was constructed for doxorubicin (DOX) and tumor-associated macrophage (TAM) polarization factor interleukin-21 (IL-21) codelivery in this study. The physicochemical properties, cytotoxicity, cellular uptake, macrophage polarization, and antitumor efficacy of functionalized nanocarriers were fully evaluated. DOX was incorporated into oxidized SWCNHs via π–π interaction (DOX-O-SWCNH) and then coated with IL-21-loaded PSL to obtain IL-21-loaded PSL (IL-21-PSL)-DOX-O-SWCNHs. The release rates of IL-21 and DOX from functionalized nanocarriers at the pH 7.4 of were lower than those at the pH of 5.5, thereby indicating a pH-sensitive drug release. Blank nanocarriers showed relatively low cytotoxicity to A549 cells and 293T cells. The half maximal inhibitory concentration (IC50) value of PSL-DOX-O-SWCNHs for A549 cells was 164.85 μg/mL. The PSL-DOX-O-SWCNHs can be effectively uptaken by A549 cells and the IL-21-PSL-DOX-O-SWCNHs can significantly downregulate the expression of M2 macrophage-related factors (IL-10 levels) and upregulate that of M1 macrophage-related factors (iNOs levels). The IL-21-PSL-DOX-O-SWCNHs also showed significantly high tumor targeting and distribution and significantly low tumor volume of A549 lung cancer cell-bearing nude mice, showing the cooperating effects of DOX and IL-21. The functionalized nanocarriers were mainly distributed in the tumor tissues and liver and less in the spleen, lung, and heart of mice. In conclusion, the functionalized IL-21-PSL-DOX-O-SWCNHs showed high drug loading, excellent cellular uptake, pH-sensitive release, TAM polarization, and remarkable antitumor efficacy in vivo.
Keywords: Doxorubicin; Interleukin-21; pH-sensitive liposome; Single-walled carbon nanohorns; Tumor associated macrophages